2016
DOI: 10.1038/jp.2016.173
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular performance using myocardial deformation imaging in infants with bronchopulmonary dysplasia

Abstract: Among infants with severe forms of BPD, evidence of abnormal RV systolic function was detected with MDI, but not traditional echocardiographic or TDI measurements. Infants with severe forms of BPD may represent a particularly high-risk subgroup for decreased RV performance warranting cardiac surveillance. MDI should be considered as a method to quantitate RV function in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 56 publications
0
20
1
Order By: Relevance
“… 7) Therefore, measuring decreases in RV strain in the longitudinal direction in the presence of afterloads, such as increased pulmonary vascular resistance, would enable the sensitive detection of RVSD in preterm children. 8) Myocardial strain, indicating changes in the length of myocardial fibers, 9) is more sensitive in detecting early myocardial changes among preterm infants than are conventional echocardiographic parameters. 10) We speculated that strain parameters could sensitively detect the progression of potential RVSD among preterm children.…”
Section: Introductionmentioning
confidence: 99%
“… 7) Therefore, measuring decreases in RV strain in the longitudinal direction in the presence of afterloads, such as increased pulmonary vascular resistance, would enable the sensitive detection of RVSD in preterm children. 8) Myocardial strain, indicating changes in the length of myocardial fibers, 9) is more sensitive in detecting early myocardial changes among preterm infants than are conventional echocardiographic parameters. 10) We speculated that strain parameters could sensitively detect the progression of potential RVSD among preterm children.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the LV function of the extremely preterm infants did not change significantly during the first week of life. 11,12 Infants with BPD and/or pulmonary hypertension had evidence of abnormal RV strain and RV fractional area change 18,19 but LV strain was not affected. 18 Levy et al 18 also reported maturation of RV, LV, and septal myocardial strains in uncomplicated preterm infants was associated with increasing weight and postnatal age.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing myocardial strain, a parameter that indicates percentage of change in the length of myocardial fibers, 6) systolic and diastolic dysfunction in children in the acute phase of KD has been assessed. 7) 8) 9) Myocardial strain can be assessed with velocity vector imaging, a technique using endocardial contour tracking to determine cardiac function.…”
Section: Introductionmentioning
confidence: 99%